Analisis Semiotika Puisi “Siapakah Engkau” Karya Heri Isnaini (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research aims to describe the signs that appear in the poem entitled "Who Are You" by Heri Isnaini using a semiotic approach. The research method used is a descriptive qualitative method. The poem "Who Are You" by Heri Isnaini will be observed and then described to find out the meaning that the composer wanted to convey through icons, indexes and symbols so that the meaning can be known clearly by the author. The results of research on the poem "Who Are You" show that there are several signs that appear in the poem, including 4 icon signs, 3 index signs, and 6 symbol signs.